2020
DOI: 10.36660/abc.20190348
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre Velocidade de Onda de Pulso e Biomarcadores Cardiovasculares em Pacientes com Fatores de Risco

Abstract: Fundamento: A relação entre velocidade de onda de pulso (VOP) e biomarcadores de mudanças estruturais do ventrículo esquerdo e artérias carótidas ainda é pouco elucidada. Objetivo: Investigar a relação entre VOP e esses biomarcadores. Métodos: Estudo transversal, retrospectivo e analítico. Revisamos prontuários médicos de pacientes com diabetes mellitus, dislipidemia, e pré-hipertensão ou hipertensão, que realizaram medida de pressão arterial central (PAC) utilizando o Mobil-O-Graph®, e doppler de carótida ou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Our study revealed that patients with carotid plaques had higher levels of aortic PWV (mean 1.54 m/s) and IMT (mean 7.653 mm), while their EF (mean 57.6%) and triglycerides (mean 101.8 mg/dl) were significantly lower compared to non-carotid plaques group. In agreement with our result, a study by Fagundes et al (16) on individuals with DM, dyslipidemia, pre-hypertension, or hypertension investigated the connection between PWV and indicators of structural alterations in the carotid arteries and left ventricle. The results showed that patients with carotid plaque had a significantly higher PWV with a p-value of less than 0.0001*.…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed that patients with carotid plaques had higher levels of aortic PWV (mean 1.54 m/s) and IMT (mean 7.653 mm), while their EF (mean 57.6%) and triglycerides (mean 101.8 mg/dl) were significantly lower compared to non-carotid plaques group. In agreement with our result, a study by Fagundes et al (16) on individuals with DM, dyslipidemia, pre-hypertension, or hypertension investigated the connection between PWV and indicators of structural alterations in the carotid arteries and left ventricle. The results showed that patients with carotid plaque had a significantly higher PWV with a p-value of less than 0.0001*.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the estimation of PWV was based on the Dyna Mapa AOP® oscillometric device based on its advantages and accessibility in our community ( 12 , 14 , 15 ). Besides it, there is a series of longitudinal studies showing a good correlation with target organ lesions and cardiovascular events with oscillometric devices ( 20 22 ), when compared to the gold standard noninvasive method of carotid-femoral tonometry ( 15 ). The differences observed between our data and the study by Oliveira et al ( 12 ) could be related, at least partially, by regional and ethnical variations in the Brazilian population ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AH treatment guided by central BP parameters has the potential to show greater effectiveness in preventing or even regressing stiffness and TOD when compared to the conventional strategy ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%